Perineal Groove: A Rare and Benign Anorectal Malformation - Ramar, P; Shringi, S (Journal of Nepal Paediatric Society, 2015)
A female neonate born at term, to 30 year old mother, with no antenatal risk factors or teratogenic exposure. On examination birth weight was 3 kgs, baby had moist, reddish mucosal groove extending from fourchette to anal verge. External genitalia were phenotypic female. No palpable mass in inguinal region or per abdomen. No dysmorphic features. Other systems were normal. Baby passed meconium and urine through normal orifices within first 24 hours. J Nepal Paediatr Soc 2015;35(1):94-95